2019
DOI: 10.9734/ajbgmb/2019/v2i230054
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Efficacy of Phytochemical Content of Corchorus olitorius Leaves against Acute Ethanol-induced Oxidative Stress in Wistar Rats

Abstract: Aim: This study is aimed at investigating the ameliorative efficacy of methanolic extract of Corchorus olitorius leaves against acute ethanol-induced oxidative stress in Wistar rats. Methods: Fresh plants of C. olitorius were harvested from the Institute of Agricultural Research and Training, Ibadan. The leaves were dried and extracted using soxhlet apparatus and methanol as the solvent. The methanol was evaporated in a rotary evaporator at 35°C with a yield of 2.17 g which represents a percentage yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Although, the activities of enzymes were not investigated in this study, but it is possible that C. olitorius leaves decreased the activity of 3hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase (the rate-limiting enzyme in cholesterol biosynthesis) [16]. C. olitorius leaves have also been reported to ameliorate the effect of ethanol-induced oxidative stress [57].…”
Section: Discussionmentioning
confidence: 96%
“…Although, the activities of enzymes were not investigated in this study, but it is possible that C. olitorius leaves decreased the activity of 3hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase (the rate-limiting enzyme in cholesterol biosynthesis) [16]. C. olitorius leaves have also been reported to ameliorate the effect of ethanol-induced oxidative stress [57].…”
Section: Discussionmentioning
confidence: 96%
“…They were air dried at room temperature in an open laboratory space for 21 days and milled into powder using an electronic blender (Moulinex). The extraction was done using soxhlet apparatus and ethanol as the solvent according to the methods described by Airaodion et al [16]. About 25 g of the powder was packed into the thimble of the soxhlet extractor and 250 mL of ethanol was added to a round bottom flask, which was attached to the soxhlet extractor and condenser on a heating mantle.…”
Section: Collection and Extraction Of Plant Materialsmentioning
confidence: 99%
“…As presented in Table 1, results from the assessment of oxidative stress markers showed ethanol-induced oxida- tive stress, based on the elevated levels of malondialdehyde and reduced glutathione, SOD and catalase in the cerebellar samples. Previous studies have also reported that ethanol has induced oxidative stress in various parts of the brain [13,14]. Ethanol is a known disruptor of the oxidative balance, by promoting oxidative stress and disrupting normal neuronal activities, thereby triggering neurodegeneration [15].…”
Section: Discussionmentioning
confidence: 97%